2018
DOI: 10.1038/s41598-018-34871-0
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer Binding Protein β inhibits myogenic differentiation via ID3

Abstract: Myogenesis is regulated by the coordinated expression of muscle regulatory factors, a family of transcription factors that includes MYOD, MYF5, myogenin and MRF4. Muscle regulatory factors are basic helix-loop-helix transcription factors that heterodimerize with E proteins to bind the regulatory regions of target genes. Their activity can be inhibited by members of the Inhibitor of DNA binding and differentiation (ID) family, which bind E-proteins with high affinity, thereby preventing muscle regulatory factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 31 publications
6
30
0
Order By: Relevance
“…However, whether homo/heterodimers of BmC/EBPg activate BmCBP expression requires further investigation. C/EBPs are also well-known CCAAT/EBPs and are widely reported to be involved in many cellular processes, such as cell growth and aging (Buck et al, 1999;Schafer et al, 2018), differentiation Radomska et al, 1998;AlSudais et al, 2018;Jeong et al, 2019), injury and inflammation response (Burgess-Beusse and Darlington, 1998;Poli, 1998;Jo et al, 2018), and cellular phenotypes (Lekstrom-Himes and Xanthopoulos, 1998;Salaroglio et al, 2018). In mammals, C/EBPs play pivotal roles in immunoresponse (Dai et al, 2017;Larabee et al, 2018), inflammatory response, liver regeneration, metabolism and numerous diseases (Ramji and Foka, 2002;Pulikkan et al, 2017;Wattanavanitchakorn et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether homo/heterodimers of BmC/EBPg activate BmCBP expression requires further investigation. C/EBPs are also well-known CCAAT/EBPs and are widely reported to be involved in many cellular processes, such as cell growth and aging (Buck et al, 1999;Schafer et al, 2018), differentiation Radomska et al, 1998;AlSudais et al, 2018;Jeong et al, 2019), injury and inflammation response (Burgess-Beusse and Darlington, 1998;Poli, 1998;Jo et al, 2018), and cellular phenotypes (Lekstrom-Himes and Xanthopoulos, 1998;Salaroglio et al, 2018). In mammals, C/EBPs play pivotal roles in immunoresponse (Dai et al, 2017;Larabee et al, 2018), inflammatory response, liver regeneration, metabolism and numerous diseases (Ramji and Foka, 2002;Pulikkan et al, 2017;Wattanavanitchakorn et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…1D). Since C/EBPb is an inhibitor of myogenesis 9,10 , the detection of the 23 kDa band correlates with myogenic differentiation (detected only in differentiating myoblasts) and not with C/EBPβ expression ( Fig 1C and D). The 23 kDa band was successfully precipitated using the anti-C/EBPb antibody but not by the control IgG as detected by silver staining ( Fig.…”
Section: Anti-c/ebpβ Antibody (Ab32358) Detects a Non-specific Band Imentioning
confidence: 94%
“…In healthy muscle, satellite cells express C/EBPb which inhibits myogenic differentiation 9,10 . Upon induction of differentiation, C/EBPβ expression dramatically decreases, allowing differentiation to proceed [9][10][11] . We observed that the anti-C/EBPb antibody (E299, ab32358) also detects myosin light chain 4 (MYL4) in differentiating myoblasts and in other cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…to proceed [9][10][11] . We observed that the anti-C/EBP antibody (E299, ab32358) also detects myosin light chain 4 (MYL4) in differentiating myoblasts and in other cell lines.…”
Section: Upon Induction Of Differentiation C/ebpβ Expression Dramatimentioning
confidence: 99%
“…In response to muscle injury, satellite cells become activated, proliferate, differentiate and fuse to form myofibers that express contractile proteins 8 . In healthy muscle, satellite cells express C/EBP which inhibits myogenic differentiation 9,10 .…”
Section: Introductionmentioning
confidence: 99%